Workplace culture in psychiatric nursing described by nurses. Issue 4 (24th April 2017) - Kurjenluoma, K.; Rantanen, A.; McCormack, B.; Slater, P.; Hahtela, N.; Suominen, T.
Abstract : Aim: This study looks to describe the workplace culture from the viewpoints of stress, job satisfaction and practice environment. Methods: Data were collected from nurses (n = 109) using a web‐based survey, The Person‐Centred Nursing Index, from two purposefully selected hospital districts in Finland. Data were statistically analysed. Results: Nurses described their workplace culture in slightly positive terms. Nurses only occasionally experienced stress (mean = 2.56, SD = 0.55) and were fairly satisfied with their job (mean = 4.75, SD = 0.66) and their practice environment (mean = 4.42, SD = 0.81). Demographic variables such as the nurses' age, length of time in nursing, time at their present hospital, working shifts and their use of patient restriction were more frequently associated with their perceived workplace culture. Conclusion: Older nurses and those with a longer work history in the nursing profession tended to be more satisfied with their workplace culture in psychiatric nursing. Young and/or newly graduated nurses felt more negatively on their workplace culture; this issue should be recognised and addressed with appropriate support and mentoring. Nurses who used restrictive measures were more often less satisfied with their workplace culture. Continuous efforts are needed to reduce the use of coercive measures, which challenge also the managers to support nursing practice to be more person‐centred.